The engaged caregiver how to build a performance-driven workforce to reduce burnout & transform care - Cabral, Joseph; Lee, Thomas H.; Wright, Martin (McGraw-Hill, 2020)
"From the top experts on healthcare workforce engagement comes the vital road map to reduce the alarmingly high-and fast-growing-rate of staff burnout and to transform care. More than half of U.S. physicians and 40 percent of nurses experience one or more symptoms of burnout. This crisis poses a serious threat to our health systems, impacting not only the well-being of the caregiving workforce but also that of patients. Written by a team of thought leaders with deep expertise in healthcare workforce engagement and cultural development, The Engaged Caregiver offers a detailed guide for leaders, managers, and front-line providers to identify, diagnose, measure, and develop strategies to address and overcome caregiver burnout. It's an actionable plan for developing and building a resilient culture that empowers caregivers and gives them the support they need to fulfill the patient promise with every care experience, every day"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Medical personnel -- Job stress; Medical personnel -- Personnel management; Caregivers -- Job stress; Burn out (Psychology); Physicians -- psychology; Nurses -- psychology; Physicians -- organization & administration; Nurses -- organization & administration; Burnout, Professional; Personnel médical; Stress dû au travail; Personnel médical; Personnel; Direction; Aidants naturels; Stress dû au travail; Épuisement professionnel; BUSINESS & ECONOMICS / Industries / Pharmaceutical & Biotechnology; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Customer Relations; MEDICAL / Administration; MEDICAL / Caregiving; MEDICAL / Education & Training; MEDICAL / Health Care Delivery; MEDICAL / Hospital Administration & Care; MEDICAL / Physician & Patient; Caregivers; Job stress; Medical personnel; Job stress